Nebulized fluticasone propionate, a viable alternative to systemic route in the management of childhood moderate asthma attack: A double-blind, double-dummy study - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (W B SAUNDERS CO LTD, 2015)
Background: In this study, we compared the clinical and immunological efficacy of nebulized corticosteroid (CS) to systemic route during treatment of moderate asthma attack in children. Methods: In this randomized, placebo-controlled, double-blind, double-dummy, prospective study, 81 children aged 12 months to 16 years experiencing asthma attack randomized into two treatment groups to receive, either; nebulized fluticasone propionate (n = 39, 2000 mcg/day) or oral methylprednisolone (n = 41, 1 mg/kg/day). Pulmonary index scores (PIS) were assessed at admission and at 1st, 4th, 8th, 12th, 24th, 48th hours, as well as, on day 7 and peak expiratory flow (PEF) at baseline and at the 7th day. Daily symptom and medication scores were recorded for all subjects. Immunological studies included phytohemagglutinin induced peripheral blood mononuclear cells culture supernatant for cytokine responses and CD4(+) CD25(+) FOXP3(+) T regulatory cell (T reg) percentage at baseline and day 7. Results: The changes in PIS and PEF were similar in both treatment groups, with a significant improvement in both values at the 7th day, when compared to baseline. In both groups, significant reductions in symptom and medication scores were observed during the treatment period with no significant difference between the groups. At day 7 of intervention, phytohemagglutinin induced IL-4 level was significantly decreased only in the nebulized group compared to baseline (p = 0.01). Evaluation of cytokine responses by means of fold increase (stimulated (S)/unstimulated (US) ratio) revealed a significant reduction in IL-4, IL-5 and IL-17 only in nebulized group (p = 0.01, 0.01, 0.02; respectively). The fold increase value of IL-5 was significantly lower at 7th day in nebulized group when compared to systemic one (p = 0.02). At 7th day, although in both treatment groups the percentage of T reg cells was suppressed, it remained significantly higher in the nebule one when compared to systemic route (p = 0.04). Conclusion: In the management of moderate acute asthma attack, nebulized CS (2000 mcg daily) was found to be as effective as systemic route with regard to clinical improvement. In addition, immunological parameters were more in favor of nebulized route which may imply a salutary effect of local CS usage. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Nebulizer corticosteroid; Acute asthma attack; Children; REGULATORY T-CELLS; INHALED CORTICOSTEROIDS; ORAL PREDNISOLONE; CHILDREN; BUDESONIDE; EXPRESSION; CYTOKINE; EXACERBATION; THERAPY; ADJUNCT